Factors associated with psychotropic drugs use in older adults hospitalized in clinical and surgical wards of a university hospital - Rafael Thomazi; Carlos Alberto dos Santos Filho; Alessandro Ferrari Jacinto (Dementia & Neuropsychologia, 2025)
ABSTRACT. Prescription of psychotropic drugs and potentially inappropriate medications (PIMs) for older adults is a common condition. Assessing the factors associated with this prescription is essential especially within the hospital setting, requiring the implementation of strategies for promoting rational use of medications in this age group. Objective: To evaluate factors associated with the use of psychotropic drugs in hospitalized older adults. Methods: Cross-sectional study, conducted at Hospital das Clínicas de Botucatu, Brazil. Patients were divided into clinical patients taking or not taking psychotropic drugs and surgical patients taking or not taking psychotropic drugs. Multivariate analysis was performed, adopting "use or non-use of psychotropic drugs" and "having geriatrician as prescriber before hospitalization or otherwise", as dependent variables. Results: Of the 385 participants, 60% practiced polypharmacy and 55% were in use of PIM. Clinical patients using psychotropic drugs took more PIM (p<0.001) and more medications (p=0.002) than non-users. For the total sample, PIM use was associated with a 4.53 times greater chance of taking psychotropic drugs, and each additional medication used was associated with a 1.15 times greater chance of taking psychotropic drugs. Being accompanied by a geriatrician before hospital admission was associated with a 4.0 times greater chance of no PIM being prescribed. Conclusion: PIM use and polypharmacy were associated with an increased chance of taking psychotropic drugs. Being accompanied by a geriatrician before hospitalization was associated with a lower chance of PIM use.